Bimodal onset and pan-cancer uniformity of immune-mediated liver injury: a retrospective cohort study - Song, Jiaojiao; Xu, Biying; Yu, Lan; Fu, Haiwei; Wang, Binliang; Zhou, Mo; Hu, Yumin; Xia, Yang (Frontiers in Immunology, 2025)
BackgroundImmune-mediated liver injury (IMLI) is a critical adverse event in patients treated with PD-1/PD-L1 inhibitors. The study aims to characterize the clinical heterogeneity, temporal dynamics, and immunological drivers of PD-1/PD-L1 inhibitor-associated IMLI and optimize surveillance and management strategies.MethodsWe retrospectively recruited 373 IMLI patients. We evaluated clinical data, including liver injury patterns, severity, temporal trends, and immune cell subsets. Statistical analyses identified risk factors for severe IMLI and temporal dynamics.ResultsAmong 373 patients (median age: 65 years; male: 74.8%), IMLI severity was graded as G1 (53.9%), G2 (25.2%), G3 (17.9%), and G4 (2.7%), with hepatocellular (17.2%), mixed (42.6%), and cholestatic (40.2%) patterns observed. The median time to onset was 106–115 days across severity groups. In contrast, recovery time was significantly prolonged (G1/2: 14 days vs. G3/4: 23 days, P<0.05), and recovery-phase CD8+ T cells (524.9 vs. 270.68 cells/μL, P=0.026) were higher in severe cases. Bimodal onset peaks occurred at 1–2 months and 3–4 months, with 88% recovering within 100 days. No tumor-type differences existed in patterns (P=0.427) or severity (P=0.054). Elevated baseline NK cells (OR=1.004, P=0.036) predicted severe IMLI.ConclusionsIMLI demonstrates bimodal onset and pan-cancer uniformity, driven by systemic immune dysregulation. Baseline NK cells are potential predictors of severity. Risk-adapted monitoring within 4 months post-ICI and standardized protocols are recommended.